Use of Extra-School Time and Child Behaviours: Evidence from the UK - Elena Claudia Meroni; Daniela Piazzalunga; Chiara D. Pronzato (Institute of Labor Economics (IZA), 2018)
In this paper, we study the effects of extra-school activities on children's non-cognitive development, using data from the Millennium Cohort Study (UK) and focusing on children aged 7-11 years old. We classify the time spent out of school into six homogenous groups of activities, using principal component analysis, and estimate the relationship thereof with five behavioural dimensions drawn from the Strength and Difficulties questionnaire, exploiting the panel structure of the data. Results show the beneficial effects on children's behaviour of sports, school-related activities, time with parents and household chores, while a small detrimental effect of video-screen time is detected. We test the robustness of our estimates against omitted variable bias, and the results are confirmed. We also observe that children from more advantaged backgrounds have easier access to more beneficial activities. Overall, our results suggest that different uses of time may reinforce inequalities across children from different backgrounds.
Keywords: J13; D1; 330; child time use; extra-curricular activities; Strengths and Difficulties questionnaire; longitudinal data; Millennium Cohort Study; non-cognitive development; omitted variable bias